2005
DOI: 10.1021/jp050713+
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Labeling Effects in Confocal Laser Scanning Microscopy

Abstract: Confocal laser scanning microscopy (CLSM) is being increasingly used for observing protein uptake in porous chromatography resins. Recent CLSM studies have revealed the possible existence of a nondiffusive protein transport mechanism. Observing protein uptake with CLSM requires labeling the protein with a fluorescent probe. This study examines the effect of the probe identity on the subsequent CLSM adsorption profiles. The adsorption of lysozyme conjugated with different fluorescent probes (Cy5, BODIPY FL, Att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 21 publications
2
60
0
Order By: Relevance
“…Confocal microscopy results for a basic protein (lysozyme) labeled with acidic fluorophores clearly show diffuse fronts at higher ionic strengths despite the presence of labeled and unlabeled proteins as well as relatively sharp isotherms [19]. Therefore, the presence of a diffuse front in this system appears to be a reliable indicator of a homogeneous diffusion mechanism, and the results of Teske et al [57] suggest that this will be the case whenever the labeled protein is less strongly retained than the unlabeled one. Additional support for inferring a change in uptake mechanism that reflects an increase in the uptake rate is provided by uptake measurements on pure unlabeled protein in batch and breakthrough experiments; some additional data of this kind are presented below.…”
Section: Ribonucleasementioning
confidence: 82%
See 2 more Smart Citations
“…Confocal microscopy results for a basic protein (lysozyme) labeled with acidic fluorophores clearly show diffuse fronts at higher ionic strengths despite the presence of labeled and unlabeled proteins as well as relatively sharp isotherms [19]. Therefore, the presence of a diffuse front in this system appears to be a reliable indicator of a homogeneous diffusion mechanism, and the results of Teske et al [57] suggest that this will be the case whenever the labeled protein is less strongly retained than the unlabeled one. Additional support for inferring a change in uptake mechanism that reflects an increase in the uptake rate is provided by uptake measurements on pure unlabeled protein in batch and breakthrough experiments; some additional data of this kind are presented below.…”
Section: Ribonucleasementioning
confidence: 82%
“…Initial arguments invoked electrokinetic phenomena in various forms [19,54], but more recent theoretical and experimental studies in various groups have implicated displacement mechanisms involving labeled and unlabeled proteins [55][56][57]. Specifically, conjugation of a label such as Cy5 to a protein via a lysine residue replaces a positive charge at neutral pH by a negative charge, making the charge on the labeled protein different to that on the unlabeled one by -2.…”
Section: Ribonucleasementioning
confidence: 99%
See 1 more Smart Citation
“…For example, early studies that applied CLSM to ion-exchange chromatography revealed the existence of an unexpected concentration 'overshoot' phenomenon (Dziennik et al, 2003;Hubbuch et al, 2002Hubbuch et al, , 2003, which initially was attributed to a novel non-diffusive protein transport mechanism (Dziennik et al, 2003;Liapis et al, 2001). Recent experimental and modeling studies have, however, cast doubt upon these early interpretations by revealing how protein displacement during competitive adsorption can explain the obtained intraparticle concentration profiles (Martin et al, 2005;Teske et al, 2005Teske et al, , 2006. Experimentally, bio-conjugates are diluted with a high fraction of the native protein species in order to ensure signal linearity.…”
Section: Introductionmentioning
confidence: 99%
“…However, the quantitative interpretation is often complicated by artifacts arising from the different adsorptive behavior of native and fluorescently labeled protein molecules and by fluorescence attenuation effects. 9,16 Refractive index microscopy, as recently introduced, 11,12 allows measurements with unlabeled proteins but is restricted to cases where the concentration profile is very sharp. Finally, light microscopy with gels supported in square capillaries can provide quantitative insight, but requires special syntheses and is cumbersome when the gel is produced through a multistep process, such as is the case for charged agarose gels.…”
Section: Introductionmentioning
confidence: 99%